Pharmacological and toxicological evaluation of Alpinia speciosa - V. L. M. Mendonça; C. L. A. Oliveira; A. A. Craveiro; V. S. Rao; M. C. Fonteles (Memorias do Instituto Oswaldo Cruz, 1991)
Alpinia speciosa Schum or A. nutans is a plant of the Zingiberanceae family, Known popularly as "colony" (colônia) and used as a diuretic and to control hypertensión. We have determinated the concentration of Na+ and K+ found in the alcoholic extract and in the tea concoction. They contained 51.0mEq Na+, and 132 mEq K+ in the extract, and 0,0 mEq of Na+ and 26 mEq K+ in the tea. Phytochemical analysis of the leaves demonstrated the presence of catecquic tanins, phenols and alkaloids, and also some essential oils. When injected intra-peritoneally the hydroalcoholic extract, in range of 100 a 1400 mg/Kg, (or 2500-18000 mg/Kg orally) produced in mice: writhing, psychomorot excitation, hypokinesis and pruritus. The LD50 by ip was 0.760 + or - 0.126 g/Kg and 10.0 + or - 2.5 g/Kg by oral administration for the hydroalcoholic extract. Subacute toxicity made injecting daily for 30 days the LD10 in rats caused an increase in transaminases and lactate dehydrogenase, whereas other parameters such as nlood glucose, urea and creatinine were normal. A histopathological analysis of liver, spleen, gut, lung and heart showed no alterations. The drug also produced a prolongation of the sleeping time. The hydroalcoholic extract induced int he rat and in the dog a dose-dependent fall in blood pressure in doses of 10 to 30 mg/Kg. In isolated atria the extract induced a reduction of the frequnecy and in the inotropic responses. Neither the extract nor the tea had an effect on the diuresis of the rat.